Hybrid Approaches for Advanced Medical Text Summarization: Combining TF-IDF, BERT, and Seq2Seq Models - Matimpati Chitra Rupa; Ramani, Kasarapu (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Clinicians, researchers, and healthcare professionals are confronted with the challenge of efficiently extracting relevant knowledge from vast amounts of textual data. Medical text summarization emerges as a crucial tool to address this challenge by condensing lengthy medical documents into concise, informative summaries. A comprehensive hybrid approach is proposed to address the challenges in medical text summarization by combining both extractive and abstractive methods, by integrating Term Frequency-Inverse Document Frequency (TF-IDF) of Natural Language Processing (NLP) and AutoModelForSeq2SeqLM of Large Language Model. The performance this proposed approach is compared with existing methods such as Bidirectional Encoder Representations from Transformers (BERT), Text Rank, K-means, face book BART-Large-CNN, GPT2 using ROUGE-1, ROUGE-2 and ROUGE-L metrics. The experimental results show that hybrid approach is outperforming other existing methods. Medical text summarization helps extract important information from large medical documents. This work combines two methods, TF-IDF and AutoModelForSeq2SeqLM, to create better summaries, performing better than existing techniques like BERT and GPT-2 based on ROUGE scores.